Research and development of the device for diagnostics of arrhythmia; Journal of Physics: Conference Series; Vol. 881 : Innovations in Non-Destructive Testing (SibTest 2017) - Lezhnina I. A. Inna Alekseevna; Boyakhchyan A. A.; Overchuk K. V.; Uvarov A. A. Aleksandr Andreevich (2017, 2017)
Title screen